Recenzja książki: Eleanor Dickey, Ancient Greek scholarship: a guide to finding, reading and understanding scholia, commentaries. lexica and grammatical treatises, from their beginnings to the Byzantine period, Oxford University Press, New York 2007, s. 362. - Chiżyńska, Katarzyna (Collectanea Philologica, 2012)
In this volume are included two flattering reviews, first of Eleanor Dickey, Ancient Greek scholarship: a guide to finding, reading and understanding scholia, commentaries, lexica and grammatical treatises, from their beginnings to the Byzantine period (New York 2007) and the second of René Nünlist, The ancient critic at work. Terms and concepts of literary criticism in Greek scholia (New York 2009). Both reviewed works focuses on Greek scholarship and are very helpful for modern scholars with understanding ancient literary criticism and reading scholia. Scientists rarely use Greek commentaries, because of their technical and philological difficulties, especially because of particular writing and vocabulary, used by scholiasts. There are very few works concerning this theme, so any new published results of researches this kind is priceless. Moreover both reviewed works are of highest scientific level.